Which Are the Cells of Origin in Merkel Cell Carcinoma? - Thomas Tilling; Ingrid Moll (Journal of Skin Cancer)
Merkel cell carcinoma (MCC), a highly aggressive skin tumour with increasing incidence, is associated with the newly discovered Merkel cell polyomavirus (MCPyV). Studies on MCC and MCPyV as well as other risk factors have significantly increased our knowledge of MCC pathogenesis, but the cells of origin, which could be important targets in future therapies, are still unknown. Merkel cells (MCs), the neuroendocrine cells of the skin, were believed to be at the origin of MCC due to their phenotypic similarities. However, for several reasons, for example, heterogeneous differentiation of MCCs and postmitotic character of MCs, it is not very likely that MCC develops from differentiated MCs. Skin stem cells, probably from the epidermal lineage, are more likely to be cells of origin in MCC. Future studies will have to address these questions more directly in order to identify the physiological cells which are transformed to MCC cells.